Religião de matriz africana em São José de Ribamar/MA e a experiência de visitação acadêmica - Linda Maria Rodrigues; Elizandra Rocha (Confins)
This article aimed to report the academic experience held at the Terreiro de Mina Nanã Buruque located in the City of São José de Ribamar / Ma. A technical visit was made to during the celebration of Nossa Senhora Sant'Ana, through the discipline of Fundamentals of Tourism II of the undergraduate course in Tourism / UFMA. The African Matrix religions maintain an annual calendar of activities, called “obligation”, mixed with activities of an internal nature, and activities aimed at community participation, always with strong ties to popular culture. The methodology used was bibliographic research and field research combined with the objectives and methodology of the discipline, which considered an analysis of the so-called region that generates visitors (the City of São Luís) by a transit route (departure and arrival) to the inducing municipality of tourists (the City / Terreiro). Through prior authorization from the Priest, responsible for the Terreiro, the visit was made. It was concluded that, learning about the African Matrix Religions as a reaffirmation of a culture of social resistance and African religiosity in Maranhão was of fundamental importance for the students of the Tourism Course and also for an understanding of those responsible for the Terreiro and the local community, as a reaffirmation of the differences and the possibilities of opening for the generation of self-sustainable itineraries. The Terreiros were identified as spaces of memory, which bring identity traits of cultural resistance of peoples and ethnic groups in Maranhão, as a real possibility of visibility and balanced conduction of future markets for the sector.